2019
DOI: 10.3390/agronomy9090531
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biochar on Physicochemical Properties of Haplic Luvisol Soil under Different Land Use: A Plot Experiment

Abstract: There is limited information regarding the effect of biochar (BioC) on improving the fertility of degraded soils (fallow and grassland), particularly with respect to changes with time. The objective of the study was to evaluate, in a three-year field experiment, the influence of BioC on the physicochemical properties of Haplic Luvisol. BioC, obtained via wood waste pyrolysis at 650 °C, was applied to the soil of subplots under fallow and grassland at rates of 0, 1, 2, and 3 kg·m−2. Soil samples were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…The Q HA at pH 9.0 values of HAs isolated from pure BioC were lower than those obtained from the soil, and moreover, BioC did not have an obvious effect on the Q HA values of the soil HAs. Previous studies 4 on impact of BioC on the physicochemical properties of Haplic Luvisol under different land uses, showed that BioC added to soil caused a significant increase in Q values in the last year of the experiment. Thus, we can conclude that BioC introduced OM with a variable surface charge but did not affect the soil’s Q HA .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The Q HA at pH 9.0 values of HAs isolated from pure BioC were lower than those obtained from the soil, and moreover, BioC did not have an obvious effect on the Q HA values of the soil HAs. Previous studies 4 on impact of BioC on the physicochemical properties of Haplic Luvisol under different land uses, showed that BioC added to soil caused a significant increase in Q values in the last year of the experiment. Thus, we can conclude that BioC introduced OM with a variable surface charge but did not affect the soil’s Q HA .…”
Section: Resultsmentioning
confidence: 91%
“…The properties of soils and BioC, such as the d, C org , A, pH, and Q, were presented in detail previously 4 . Briefly, soils were characterised by a typical d value for mineral soils ≈ 2.60 g cm −3 , and by a relatively low content of C org and a high content of A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Penggunaan biochar dapat memperbaiki sifat tanah dan ketersediaan unsur hara tanah dalam jangka panjang (Agegnehu et al, 2017). Penggunaan biochar dapat meningkatkan produktivitas tanah melalui perbaikan sifat fisika, kimia (Aslam et al, 2014), (Jien & Wang, 2013), (Li et al, 2018), (Mukherjee & Lal, 2013), (Shaaban et al, 2018), (Wu et al, 2017), biologi tanah (Hussain et al, 2017) dan perbaikan struktur tanah (Bista et al, 2019), (Cybulak et al, 2019) serta porositas tanah (Huang et al, 2020), (Liu et al, 2018). Aplikasi biochar sangat penting untuk meningkatkan sifat fisik dan kimia tanah asam (Dume et al, 2015).…”
Section: Pendahuluanunclassified